2014
DOI: 10.5569/2340-5104.02.02.04
|View full text |Cite
|
Sign up to set email alerts
|

La inclusión educativa desde la voz de madres de estudiantes con Trastornos del Espectro Autista en una muestra chilena

Abstract: ResumenEl objetivo del estudio es mostrar la perspectiva de madres chilenas sobre la inclusión educativa de sus hijos escolarizados en centros de educación primaria, quienes presentan un Trastorno del Espectro Autista. Se recogen evidencias, desde la voz de las familias, que pueden servir como punto de partida para reflexionar sobre cómo avanzar hacia una educación más inclusiva y cómo contribuir a mejorar los apoyos que se brindan a estudiantes con discapacidad. El estudio se enmarca en un paradigma cualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
8
0
2
Order By: Relevance
“…Ello, porque atentan contra principios reguladores y de exclusión ampliamente adoptados por el sistema educacional chileno (Drago & Paredes, 2011;García-Huidobro, 2007;González, 2003;Levin, 2011). Así, para los profesores y directivos el tránsito desde políticas de integración hacia políticas de inclusión es un proceso que demanda tiempo, convicción y participación para desarrollar una cultura escolar basada en valores inclusivos (Villegas, Simón y Echeita, 2014), así como también se trata de un proceso continuo (Kluth, Biklen, English-Sand & Smukler, 2007).…”
Section: Actitudes Personalesunclassified
“…Ello, porque atentan contra principios reguladores y de exclusión ampliamente adoptados por el sistema educacional chileno (Drago & Paredes, 2011;García-Huidobro, 2007;González, 2003;Levin, 2011). Así, para los profesores y directivos el tránsito desde políticas de integración hacia políticas de inclusión es un proceso que demanda tiempo, convicción y participación para desarrollar una cultura escolar basada en valores inclusivos (Villegas, Simón y Echeita, 2014), así como también se trata de un proceso continuo (Kluth, Biklen, English-Sand & Smukler, 2007).…”
Section: Actitudes Personalesunclassified
“…Nevertheless, even if well-intentioned staff fear they lack the necessary knowledge and training to support pupils with SEND (Sanhueza Henríquez et al 2013;San Martín et al 2017), especially those who are autistic (Cerreta 2018;Villegas Otárola et al 2014), a strong programme of inclusion has been shown to reduce any negative effects, should they exist from an academic perspective, of the presence of pupils with SEND (Contreras et al 2020). The findings from this study also provide an important indicator of the value of engaging directly with pupils on SIP programmes and, as far as autistic children and young people are concerned, of supporting their sensory, emotional and social needs in school.…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention should be paid to the impact of earthquake tremors on autistic children and young people, not only in Chile, but in other at-risk areas (Valenti et al 2012). In addition, notwithstanding the socio-economic pressures faced by Chile which impact on schools (Santiago et al 2017), more resources are needed to enable schools to carry out the necessary planning and supervision (Cerreta 2018), to develop better school/parent relationships (Sanhueza Henríquez et al 2013;Villegas Otárola et al 2014) and engagement with the local community (Poblete-Christie, López & Muñoz 2019). Moreover, given that there is a clear need for much more research into the perspectives of autistic pupils in schools in Chile, as well as those with other areas of SEND (López et al 2014), we suggest that in tandem with the 'top down' approach from government, autistic children and young people should be provided with a say on the design and layout of their learning environment (McAllister & Sloan 2016;Scott 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the first aspect, several authors highlight the right of vulnerable students to be attended by qualified professionals who understand and respond to their educational needs [42][43][44]. Likewise, various studies stress the need to ensure that schools are truly adapted and designed to embrace all types of students, without exception, in response to the right to an inclusive and quality education for all [44][45][46]. However, studies such as that of Navarro et al [47] indicate that the various supports and structures established by the school administration to address any student's vulnerability are not working in a fully satisfactory manner for families.…”
Section: Introductionmentioning
confidence: 99%